Sex, ‘soaps’ and HIV - Natalie Ridgard (Communicare)
The phenomenon of multiple and concurrent partnerships (MCPs) is a key driver of the South African HIV epidemic. Given that the epidemic is stabilising though not yet declining, reducing the frequency of MCPs should constitute part of South Africa’s prevention strategy. Soap operas, with their strong emphasis on sexual intrigue and infidelity, offer an ideal platform for addressing the risk of MCP. This article presents quantitative research that explores the extent to which seven locally broadcast soap operas include sex and HIV in their storylines. It also explores whether a connection is currently being made between MCPs and the risk of HIV infection. The findings show that sex is a key component of these soap operas, but is only linked to HIV in two per cent of cases. In comparison with their real-world occurrence, MCPs, transactional sex and intergenerational relationships are overrepresented in soap operas. Only eight per cent of soap operas mention HIV, whether linked to sex or not. This is mostly through storylines featuring ‘stock’ HIV-positive characters. These findings feed into a wider discussion around the role and responsibilities of soap operas in a society grappling with a widespread HIV epidemic.